Cerebral Low-Molecular Metabolites Influenced by Intestinal Microbiota: A Pilot Study - Matsumoto, Mitsuharu; Kibe, Ryoko; Ooga, Takushi; Aiba, Yuji; Sawaki, Emiko; Koga, Yasuhiro; Benno, Yoshimi (Frontiers in Systems Neuroscience, 2013)
Recent studies suggest that intestinal microbiota influences gut-brain communication. In this study, we aimed to clarify the influence of intestinal microbiota on cerebral metabolism. We analyzed the cerebral metabolome of germ-free (GF) mice and ex-germ-free (Ex-GF) mice, which were inoculated with suspension of feces obtained from specific pathogen free mice, using capillary electrophoresis with time-of-flight mass spectrometry (CE-TOFMS). CE-TOFMS identified 196 metabolites from the cerebral metabolome in both GF and Ex-GF mice. The concentrations of 38 metabolites differed significantly (p < 0.05) between GF and Ex-GF mice. Approximately 10 of these metabolites are known to be involved in brain function, whilst the functions of the remainder are unclear. Furthermore, we observed a novel association between cerebral glycolytic metabolism and intestinal microbiota. Our work shows that cerebral metabolites are influenced by normal intestinal microbiota through the microbiota-gut-brain axis, and indicates that normal intestinal microbiota closely connected with brain health and disease, development, attenuation, learning, memory, and behavior.